A critical overview of Islamic Performance Bonds - Amareen, Emad Mohammad Al; Al-Husban, Mustafa M. (Faculty of Law, University of Muhammadiyah Malang, 2024)
Banks might finance international trade activities, including import and export, through letters of credit and letters of guarantee (performance bonds). This contract provides a high level of safety and stability for international trade because of the banks' unwavering assurances. This research intends to determine the degree to which Islamic Shariah regulations are followed by Islamic banks' activities while outlining the challenges these institutions face while using performance bonds. This study has highlighted the performance bond issues that importers and exporters are dealing with and has proposed solutions to the issues. This research uses a qualitative and doctrinal legal approach to investigate the structure of Islamic banks in relation to Islamic economic restrictions. This study analyses the organization of Islamic banks regarding Islamic economic controls. It also examines, how far Islamic banks can benefit from the blockchain and smart contract technology to harmonize Islamic economic controls with Islamic banks' practice in such funding & guarantees instruments. Concerning the Islamic letter of credit, the findings reveal that Islamic banks face many risks resulting from the conditions and controls set by the Islamic Trade Guidelines. Therefore, Islamic banks can face more risks than conventional banks due to the nature of Islamic finance, which prohibits dealing with interest (Ribā) and conventional insurance. furthermore, the study reveals that Blockchain Technology and smart contract has a Positive Impact on Islamic banking practise.